Initial productivity and genetic parameters of three corymbia species in brazil: Designing a breeding strategy - de Araujo, Marcio José [UNESP]; Lee, David John; Tambarussi, Evandro Vagner; de Paula, Rinaldo Cesar [UNESP]; da Silva, Paulo Henrique Muller (Canadian Science Publishing, 2021)
The survival, initial productivity, and the genetic parameters of Corymbia citriodora subsp. citriodora (CCC), Corymbia citriodora subsp. variegata (CCV), and Corymbia torelliana (CT) were used to develop a breeding strategy for the Corymbia species. Survival, height, and diameter at breast height (DBH) data were assessed 24 and 36 months after planting, and the mean annual volume increment was estimated in three trials. Longitudinal DBH data analysis was applied individually to each trial to identify the best and the poorest families at both ages. The mortality ranged from 5% in CT to 27% in CCC, and the mean annual increment varied from 17.8 to 20 m3·ha 1·year 1 at 36 months after planting. The 36-month narrow-sense heritability (h2a) was high for CCV (0.69 6 0.17), moderate for CCC (0.41 6 0.11), and low for CT (0.21 6 0.09). The genetic parameters indicated the need for different breeding strategies for each species. Selecting the best families while roguing the poor families allowed forward selection of CCC and CCV. It was possible to select good CT trees for hybrid breeding; however, improving the species population requires focusing on increasing the effective size and expanding the genetic variability in the CT population.
Keywords: BLUP; Genotypic value; Heritability; Multiple traits; Tree breeding